Comparison of Multiple Propagation Techniques of Dendrocalamus hamiltonii Under Nursery Conditions in Islamabad - Ullah, Inam; Malik, Sabeeqa Usman; Ahmad, Owais; Usman, Hazrat; Ullah, Zahir; Ali, Johar (Journal of Agriculture and Biology, 2025)
Bamboo, a fast-growing woody perennial grass from the Poaceae family, is widely recognized for its ecological and economic significance. Commonly referred to as "Green Gold" and "Cradle to Coffin Timber," it is used in construction, food production, charcoal manufacturing, and cottage industries. Additionally, bamboo plays a crucial role in soil conservation by enhancing biological, chemical, and physical properties. Globally, bamboo covers approximately 22 million hectares, yet research on its propagation techniques remains limited. This study investigates the propagation of Dendrocalamus hamiltonii under controlled nursery conditions using earthen beds. Bamboo culms with one, two, or three nodes were planted in sandy loam soil beds (10 × 30 ft) with three treatments and three replications, spaced three feet apart. The experiment was conducted using a randomized complete block design (RCBD) with supplemental irrigation as required. Growth parameters, including the number of tillers, leaf length, biomass productivity, and carbon sequestration were recorded daily until leaf maturity and monitored for three months. Biomass carbon content was estimated using a universal factor of 0.50. The collected data were analyzed using statistical software. Findings from this study provide insights into optimizing bamboo propagation techniques, contributing to sustainable forestry practices and carbon sequestration initiatives.
Keywords: Bamboo; macro propagation; plant growth regulators; biomass productivity; carbon sequestration